1997
DOI: 10.1111/j.1530-0277.1997.tb03847.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Similarities and Differences among Alcohol‐Preferring and ‐Nonpreferring Rats: Confirmation by Factor Analysis and Extension to Additional Groups

Abstract: Thirteen behavioral variables from six tasks were measured in alcohol-preferring (AA, FH, and P) and -nonpreferring (ANA, FRL, and NP) rat lines/strains and subjected to Factor Analysis. Four Independent factors accounted for > 90% of the variance. Defecation in the open field and ultrasonic vocalizations after an air puff were negatively correlated with alcohol intake and preference, whereas the increase in daily fluid intake in the presence of saccharin was positively correlated. Other factors could be label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
28
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 44 publications
10
28
1
Order By: Relevance
“…For example, anxiety levels and alcohol drinking seem to correlate in sP (sardinian alcohol-preferring) and in Indianapolis P (preferring) rats (Colombo et al 1995;Stewart et al 1993), but seem to be less consistently related in the Finnish alcohol-preferring AA (Alko Alcohol) rats (Tuominen et al 1990;Fahlke et al 1993;Möller et al 1997b) and in MR (Maudsley reactive) rats (Brewster 1968(Brewster , 1969Adams et al 1991;Overstreet et al 1993). This interpretation is supported by a recent factor analysis of 18 behavioral measures from nine pairs of alcohol-preferring and nonpreferring rats (Overstreet et al 1997). In this factor analysis some behavioral parameters reflecting emotionality (i.e., ultrasonic vocalization and open field defecation), loaded negatively on the factor alcohol.…”
Section: Discussionsupporting
confidence: 58%
“…For example, anxiety levels and alcohol drinking seem to correlate in sP (sardinian alcohol-preferring) and in Indianapolis P (preferring) rats (Colombo et al 1995;Stewart et al 1993), but seem to be less consistently related in the Finnish alcohol-preferring AA (Alko Alcohol) rats (Tuominen et al 1990;Fahlke et al 1993;Möller et al 1997b) and in MR (Maudsley reactive) rats (Brewster 1968(Brewster , 1969Adams et al 1991;Overstreet et al 1993). This interpretation is supported by a recent factor analysis of 18 behavioral measures from nine pairs of alcohol-preferring and nonpreferring rats (Overstreet et al 1997). In this factor analysis some behavioral parameters reflecting emotionality (i.e., ultrasonic vocalization and open field defecation), loaded negatively on the factor alcohol.…”
Section: Discussionsupporting
confidence: 58%
“…The interaction between different rat lines and behavioral measures was elegantly analyzed by Overstreet et al (11). These investigators confirmed that there are behavioral differences between several alcohol-preferring and nonpreferring rat lines/strains, with the former animals exhibiting less anxiogenic behavior than the latter, in direct contrast with earlier suggestions comparing just one pair of rat lines.…”
Section: Discussioncontrasting
confidence: 47%
“…Viglinskaya et al (10) compared several different strains of alcohol drinking and non-drinking rats in tests of anxiety and immobility and concluded that there was no correlation between alcohol consumption and measures of anxiety. An extensive study using 13 behavioral measures in alcohol-preferring and non-preferring rat lines provided mixed support for a link between alcohol drinking and emotionality or anxiety (11). Recently, a study by Fernández-Teruel et al (12) indicated that apparently there is no direct relationship between trait anxiety, which is higher in Roman low-avoidance rats compared to Roman high-avoidance rats, and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lines of rats that have been selectively bred for high ethanol consumption consume more saccharin than those bred for low ethanol consumption (Sinclair et al 1992;Overstreet et al 1993). In a multiline factor analytic study, saccharin consumption loaded on an ethanol factor (Overstreet et al 1997). Thus, there is the reciprocal condition in which high levels of ethanol intake predict an avidity for saccharin.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, the characteristic that has been selectively bred may be a general tendency to consume flavored solutions. Differences in emotionality and pain sensitivity have also been linked to ethanol (Badistov et al 1995;Kampov-Polevoy et al 1996;Overstreet et al 1997) and saccharin (Dess and Minor 1996;Dess et al 2000) consumption. There is clearly a genetic influence in bitter and sweet taste sensitivity in humans (Bartoshuk 1979;Gent and Bartoshuk 1983;Bartoshuk et al 1988;Looy and Weingarten 1992), and its relationship to drug abuse (Pelchat and Danowski 1992).…”
Section: Introductionmentioning
confidence: 95%